2022
DOI: 10.3390/nu14020334
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Status of Vitamin B12 in Slovenian Population

Abstract: Vitamin B12 deficiency poses a health concern, especially in vulnerable populations. Dietary vitamin B12 intake was obtained by two 24 h dietary recalls and food propensity questionnaires in a representative Slovenian cross-sectional food consumption survey, SI.Menu (n = 1248 subjects; 10–74 years). For a subgroup of 280 participants, data on serum vitamin B12 were available through the Nutrihealth study. The estimated usual population-weighted mean daily vitamin B12 intakes were 6.2 µg (adults), 5.4. µg (adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 97 publications
0
16
1
Order By: Relevance
“…A sub-sample of adult and elderly participants from the SI.Menu study further participated in the Nutrihealth study, where biological samples were taken to investigate diet related biomarkers. In previous papers, we focused on biomarkers related to vitamins (vitamin D [ 55 ], folate [ 60 ], and vitamin B12 [ 72 ]), while in the present study, we investigated markers of iron status, using serum ferritin, haemoglobin, and serum iron concentrations. The study results are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sub-sample of adult and elderly participants from the SI.Menu study further participated in the Nutrihealth study, where biological samples were taken to investigate diet related biomarkers. In previous papers, we focused on biomarkers related to vitamins (vitamin D [ 55 ], folate [ 60 ], and vitamin B12 [ 72 ]), while in the present study, we investigated markers of iron status, using serum ferritin, haemoglobin, and serum iron concentrations. The study results are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In adults and the elderly, the second largest dietary iron contributor was meat and meat products, but in adolescents, this was cereals and cereal products—particularly breakfast cereals. In Slovenian adolescents, this food category was also found to be an important source of folate [ 60 ] and vitamin B12 [ 72 ]. This is mainly due to the fact that such foods are often fortified with various vitamins and minerals (e.g., fortified breakfast cereals), including iron [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the biomarkers of vitamins were not considered. However, previous studies suggested that diet intake was highly correlated with B vitamin status [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a leading role in cellular metabolism, acting as cofactor in several metabolic processes such as mitochondrial metabolism and DNA methylation and synthesis. Several diseases such as megaloblastic anemia or even neuropsychiatric ones could derive from vitamin B12 deficiency [63]. In the oral phase, vitamin B12 starts to be bound to haptocorrin, a specific protein from saliva and gastric juice, but in duodenum, due to the presence of pancreatic proteases, the complex is disrupted [64].…”
Section: Discussionmentioning
confidence: 99%